PREVENTION OF INCOMPETENCE OF SUTURES OF INTESTINAL ANASTOMOSES BY THE METHOD OF PERMANENT INTRAMESENTERIC BLOCKADE AND LYMPHOTROPIC THERAPY - E. K. Agaev (Вестник хирургии имени И.И. Грекова)
The author considers results of inestigation for studying an efficiency of permanent intramesenteric (retroperitoneal) blockade and applying lymphotropic therapy for prevention of incompetence of sutures of intestinal anastomosis against the background of diffuse peritonitis and acute intestinal obstruction. An infusion was carried out 4–6 times a day with a special solution (novocain 0.5% (7 ml/kg/day); heparin (150 units/kg/days); proserin (0.03 mg/kg/day) and seftriakson (15 mg/kg/days)) in order to obtain the effect of permanent intramesenteric blockade and lymphotropic therapy. The solution is administered by droplet injection with the rate 100–120 drops a minute (80–120 ml per each infusion). Due to the application of the given method the frequency of cases of the incompetent sutures of intestinal anastomoses in patients of the main group decreased from 15.5% to 3.4% (X²=16,2; p